2018
DOI: 10.1002/ejlt.201800319
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Gallic Acid as Affected by an Extra Carboxyl Group than Pyrogallol in Various Oxidative Environments

Abstract: The antioxidant activity of gallic acid and pyrogallol is studied by the DPPH• scavenging assay and the extent of oxidation inhibition of the triacylglycerols of various unsaturated oils (olive, sunflower, and soybean) and their oil‐in‐water emulsions. The gallic acid molecules with an electron‐donating carboxylate anion are significantly stronger DPPH• scavengers than pyrogallol molecules (IC50 = 11.4 vs. 20.2 μM). Regarding the prevention of the triacylglycerols from oxidation, gallic acid is of higher activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…The three derivatives do not have the free carboxyl grouping, which leads us to conclude that the reduction in the antioxidant activity of these compounds against the DPPH free radical may be associated with this fact. These findings corroborate the data described by Rafiee et al (2018) in their studies comparing the antioxidant activity of GA with PyG. These authors observed a significant contribution of the carboxyl group of GA in the scavenging of DPPH free radicals.…”
Section: Dpph Radical Scavenging Ac Vitysupporting
confidence: 92%
“…The three derivatives do not have the free carboxyl grouping, which leads us to conclude that the reduction in the antioxidant activity of these compounds against the DPPH free radical may be associated with this fact. These findings corroborate the data described by Rafiee et al (2018) in their studies comparing the antioxidant activity of GA with PyG. These authors observed a significant contribution of the carboxyl group of GA in the scavenging of DPPH free radicals.…”
Section: Dpph Radical Scavenging Ac Vitysupporting
confidence: 92%
“…More unsaturated fatty acids generate LOOH molecules of higher polarity and, therefore, of higher levels of surface activity, facilitating their incorporation into the water–oil interfaces 25 . However, more unsaturated LOOH would be bulkier and occupy more space in the interface, decreasing their compact aggregations 26 . The value of [LOOH] IP decreased considerably when adding the antioxidants (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid is present in fruits and vegetables [66]; gallnuts, grapes, and blackberries [67]; eucalyptus species and Picea schrenkiana [68]; tea [69]; chestnuts and several berries [51]; Myriophyllum spicatum, Cynomorium coccineum, and Microcystis aeruginosa [70,71]; and black tea [72]. It has many medicinal uses such as antimicrobial [73], neuroprotection [74], antioxidant [75,76], anticancer [77,78], and antiulcer [79] uses and for cardiovascular diseases (CVDs) [80]. Furthermore, gallic acid has lipid homeostasis [81] and antihyperglycemic effects [82] and acts as a cardioprotective agent [83,84].…”
Section: Discussionmentioning
confidence: 99%